EVALUATION OF CALLINECTES CHITOSAN AS A SUPERDISINTEGRANT IN METRONIDAZOLE TABLET - Olorunsola, Emmanuel O.; Adedokun, Musiliu O.; Akpabio, Ekaete I. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of this study is to evaluate callinectes chitosan as a superdisintegrant in tablet formulation; superdisintegrants are incorporated into tablets at concentrations below 5% of tablet weight to effect prompt break-up of tablets after administration. Methods: Chitosan was extracted from shells of Callinectes gladiator. The polymer was characterized and then used as a disintegrant (in comparison with Ac-Di-Sol® and corn starch) at concentrations of 2, 4 and 8% for the formulation of metronidazole tablets. The micromeritic properties of granules; and mechanical and release properties of the tablets were studied. Results: A yield of 36.7% chitosan having degree of deacetylation of 62.7% was obtained from the crab shell. Fourier Transform Infrared absorption bands at 1495 and 3240 cm-1 typical of N-H bending and stretching respectively; and endothermic peak of 159 °C typical of melting of chitosan were obtained. No adverse interaction between the chitosan and metronidazole was observed. The disintegration times of tablets containing 2, 4 and 8% chitosan were 12.2, 10.4 and 9.3 min respectively. Conclusion: Callinectes chitosan is suitable for use as a superdisintegrant in tablets. It appears to be superior to corn starch as disintegrant although less effective compared to Ac-Di-Sol®. However, the relative cheapness and ready availability of chitosan would make it to be preferred to Ac-Di-Sol®.